Re-dispersion of gold supported on a 'mixed' oxide support. (3rd July 2015) - Morgan, Kevin; Burch, Robbie; Daous, Muhammad; Delgado, Juan-José; Goguet, Alexandre; Hardacre, Christopher; Petrov, Lachezar A.; Rooney, David W.
Abstract : The ability to reactivate, stabilize and increase the lifetime of gold catalysts by dispersing large, inactive gold nanoparticles to smaller nanoparticles provides an opportunity to make gold catalysts more practical for industrial applications. Previously it has been demonstrated that mild treatment with iodomethane ( J. Am. Chem. Soc., 2009, 131, 6973; Angew. Chem. Int. Ed., 2011, 50, 8912) was able to re-disperse gold on carbon and metal oxide supports. In the current work, we show that this technique can be applied to re-disperse gold on a 'mixed' metal oxide, namely a mechanical mixture of ceria, zirconia and titania. Characterization was conducted to guage the impact of the iodomethane (CH3 I) treatment on a previously sintered catalyst. Graphical Abstract: